Modes of Defensive Behavior in a Violent Society - Davis, Hugh; Simpson, Douglas; Knudten, Richard; Turci, Vitaliano (International journal of offender therapy and comparative criminology, 1993)
Violence has a history beginning with mankind. The study of violence indicates periodic peaks of violence. Our present time clearly suggests that violence is widespread and seemingly uncontrollable. One potential source of help is that of religion. The clergy needs to proclaim the values of morality, ethics, spirituality, and social responsibility. Since members of religion are everywhere throughout society, a basic, fundamental climate of anti-violence might begin to take root